Potentially Dangerous Behavior in the Mentally Ill: Attitudes of Journalists and Medical Students toward Compulsory Admission - Holzinger, Anita (International journal of offender therapy and comparative criminology, 2002)
Compulsory admission is a critical measure that may lead to stigmatization of patients. The authors investigated what medical students and journalists consider legitimate conditions for compulsory admission. The most frequently quoted conditions in both groups were violent attempts against others. About one third of each group considered continuous neglect as a reason. Students significantly more often than journalists advocated for civil commitment in the case of suicide attempts and violent attempts. Medical students with personal contact with mentally disordered persons advocated significantly more often for coercive measures in the case of suicide attempts. Comparing journalists and medical students having personal contact with mentally disordered persons revealed that medical students significantly more often supported commitment. Journalists displayed a more liberal attitude toward the mentally ill than did medical students